Correlation between Gibbus and Neurological Status in Patients with Tuberculous Spondylitis and its impact after Operative Intervention - Egypti, Lubna; Rahim, Agus Hadian; Ganiem, Ahmad Rizal; Ramdan, Ahmad; Dian, Sofiati (Althea Medical Journal, 2024)
Background: Tuberculous (TB) spondylitis is a chronic infectious disease associated with Mycobacterium tuberculosis that affects the spine. This disease is a challenging disease to treat due to its serious complications and high morbidity rate. Neurological deficits and spinal deformities that can occur along with gibbus are some of the most common complications. Early diagnosis and treatment are essential to cure this disease, with the administration of anti-TB drugs and operative intervention. This study aimed to analyze the correlation between gibbus and neurological status as well as the impact of operative intervention on the degree of gibbus and neurological status.Methods: This was an observational-analytic study with a cross-sectional design on 32 medical records of TB spondylitis patients who underwent operative intervention from January 2018 to December 2021 at Dr. Hasan Sadikin General Hospital. Gibbus determined by x-ray analysis and neurological status determined by the American Spinal Injury Association (ASIA) impairment scale (AIS) were examined before and after the intervention. The sample was chosen based on consecutive sampling. All data collected was tested using Spearman's correlative analysis, paired t-test, and Wilcoxon sign-rank test with a p-value <0.05 considered statistically significant.Results: There was a significant correlation between gibbus and neurological status-AIS (r=-0.708; p<0.05); and a significant positive impact of operative intervention on the degree of gibbus (p<0.05) and neurological status-AIS (p<0.05).Conclusion: There is a correlation between gibbus and neurological status-AIS. In addition, operative intervention also has a significant positive impact on the degree of gibbus and AIS, resulting in good clinical and radiological outcomes.